The mediating role of export-oriented Japanese foreign direct investment in China - Yong, C.C.; Yew, S.Y.; Teh, P.L. (2009)
Since the early nineties, China has become the largest destination of Japanese foreign direct investment (FDI). Observing this trend, we have analyzed whether Japanese FDI did promote exports from China to the rest of the world, and more importantly, whether this is a strategy adopted by Japanese multinationals to penetrate not only the Chinese market but also the global market. Our analysis takes into account, not only the direct effects of FDI on exports, but also the indirect effects, by examining the mediating role of export oriented Japanese FDI in China from 1998 to 2007 through panel analysis. The study contributes to the conceptual framework of indirect relationship among the macroeconomic variables, FDI and exports and provides some insights of export oriented Japanese FDI’s strategy in creating a win win platform for Japan and China.